2019
DOI: 10.1016/j.neulet.2017.06.018
|View full text |Cite
|
Sign up to set email alerts
|

The neuroscience of understanding the emotions of others

Abstract: We cannot help but impute emotions to the behaviors of others, and constantly infer not only what others are feeling, but also why they feel that way. The comprehension of other people’s emotional states is computationally complex and difficult, requiring the flexible, context-sensitive deployment of cognitive operations that encompass rapid orienting to, and recognition of, emotionally salient cues; classification of emotions into culturally-learned categories; and using an abstract theory of mind to reason a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 47 publications
1
38
0
2
Order By: Relevance
“…These findings call for a revisit to emotion models. For instance, the present paper has demonstrated that color can successfully communicate 18 distinct emotion categories to an observer as well as positive and negative valence, but more categories or degrees of valences are likely ( 7 , 26 ). For example, it is possible that new combinations of AUs and colors, not tested in the present study, can yield previously unidentified facial expressions of emotion.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…These findings call for a revisit to emotion models. For instance, the present paper has demonstrated that color can successfully communicate 18 distinct emotion categories to an observer as well as positive and negative valence, but more categories or degrees of valences are likely ( 7 , 26 ). For example, it is possible that new combinations of AUs and colors, not tested in the present study, can yield previously unidentified facial expressions of emotion.…”
Section: Discussionmentioning
confidence: 65%
“…For example, it is possible that new combinations of AUs and colors, not tested in the present study, can yield previously unidentified facial expressions of emotion. This is a fundamental question in emotion research likely to influence the definition of emotion and the role of emotions in high-level cognitive tasks ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…7). This post hoc analysis was decided in the light of the existing strong evidence about the role of the amygdala in the detection of ambiguous, emotion-relevant cues (65,66) and the insular cortex in the integration of internal cues, like affective state (67) and empathic processing (68,69), to the cognitive evaluation of emotional input, as well as the involvement of the orbitofrontal cortex and striatum in the neural systems mediating emotional processing (70,71).…”
Section: Different Gc Rhythms Change the Functional Connectivity Of Gmentioning
confidence: 99%
“…Grounded in extensive research in social and cognitive psychology, we conceptualised appearance‐based bias as the result of both the beholder's automatic evaluation of the hedonic valence of another's facial features, and the related activation of most basic approach/avoidance motivation systems . Such automatic inferential processing may influence the subsequent classification of emotions into discrete emotional facial expressions …”
Section: Introductionmentioning
confidence: 99%